2005
DOI: 10.1523/jneurosci.4337-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Cerebral Amyloid Angiopathy-Associated Microhemorrhage in Amyloid Precursor Protein Transgenic Mice by Immunotherapy Is Dependent on Antibody Recognition of Deposited Forms of Amyloid β

Abstract: Passive immunization with an antibody directed against the N terminus of amyloid ␤ (A␤) has recently been reported to exacerbate cerebral amyloid angiopathy (CAA)-related microhemorrhage in a transgenic animal model. Although the mechanism responsible for the deleterious interaction is unclear, a direct binding event may be required. We characterized the binding properties of several monoclonal anti-A␤ antibodies to deposited A␤ in brain parenchyma and CAA. Biochemical analyses demonstrated that the 3D6 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
243
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(262 citation statements)
references
References 44 publications
(71 reference statements)
5
243
6
Order By: Relevance
“…We have previously shown that this phenomenon is occurring following passive immunization with Aβ antibodies (Wilcock et al, 2004c). Other groups have also shown that treatment of aged APP transgenic mice with anti-Aβ antibodies results in an increased incidence of vascular microhemorrhage (Pfeifer et al, 2002;Racke et al, 2005). However, to date, this vascular adverse event has not been reported following active immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that this phenomenon is occurring following passive immunization with Aβ antibodies (Wilcock et al, 2004c). Other groups have also shown that treatment of aged APP transgenic mice with anti-Aβ antibodies results in an increased incidence of vascular microhemorrhage (Pfeifer et al, 2002;Racke et al, 2005). However, to date, this vascular adverse event has not been reported following active immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization by the same protocol also prevented cognitive deficits in both doubly transgenic APP+PS1 mice (Morgan et al, 2000) and CRND8 transgenic APP mice (Janus et al, 2000). It was later shown that passive immunization of transgenic mice using anti-Aβ antibodies resulted in significant reductions in amyloid deposition (Bard et al, 2000;Wilcock et al, 2004b), but also increased incidence of microhemorrhage (Pfeifer et al, 2002;Racke et al, 2005) associated with increased cerebral amyloid angiopathy (CAA) (Wilcock et al, 2004c).…”
Section: Introductionmentioning
confidence: 98%
“…Whereas the small fraction of systemically delivered anti-A␤ antibodies in the CSF may participate in amyloid clearance, antibodies circulating in the vasculature may be responsible for the increase in CAA. Although their overall penetration in the brain is negligible (Յ0.1%) (10,27,29), amyloid-binding anti-A␤ antibodies, when circulating in the vasculature, may be able to associate with CAA (24). Such association could increase with increasing concentrations of antibody in the vasculature and/or increasing levels of preexisting CAA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies illustrate that passive immunizations with antibodies that target amyloid plaques and reverse the cognitive deficit also increase CAA in transgenic mouse models of AD (21,22). In addition, CAA-associated microhemorrhages were augmented with such immunizations in transgenic AD models (21)(22)(23)(24). These effects of anti-A␤ immunotherapy present a significant risk in light of the fact that CAA is associated with pathological abnormalities and cognitive impairment in the elderly population, and is prevalent in Ͼ80% of patients with AD (25,26).…”
mentioning
confidence: 99%
“…Another possible side effect associated with Aβ vaccination is cerebral hemorrhages that were reported in one of AD patients subjected to the AN1792 clinical trial. Several groups [70][71][72] reported that passive immunization of anti-Aβ antibodies directed against N-terminal epitopes of Aβ and/or antibodies immunoreactive with Aβ deposits increased cerebral microhemorrhage in AD mouse models. This hemorrhage seems to be associated with passive immunization but not with active one [22].…”
Section: Discussionmentioning
confidence: 99%